First data on the carbon isotope composition of conodont elements from the Middle Permian (Kazanian Stage) of the Tchimbulat section (Vyatka Dislocations, Volga-Ural Anteclise) - Zhuravlev, A. V. (Litosfera (Ekaterinburg. Online), 2025)
Research subject . Carbon isotope composition of conodont elements of Middle Permian age from the section of the Nemda Formation in the Chimbulat quarry. Aim. Paleoecological interpretation of data on the carbon isotope composition of conodont elements from Early Kazanian deposits of the Volga-Vyatska region. Materials and Methods . Carbon isotope composition was studied in 11 conodont elements of the Stepanovites, Sweetina , and Kamagnathus genera from 9 samples. The samples characterize the Kamagnathus khalimbadzhae regional conodont zone. Results. The average carbon isotopic composition of conodont elements in the studied samples was –27.3‰, which is lower than the average value for the Devonian-Carboniferous interval of the palaeotropical realm (–26.7‰) and similar to the isotopic composition of conodonts from biohermal and near-biohermal facies of the Middle Carboniferous of Pai-Khoi. Judging by the relatively light carbon isotopic composition, the Middle Permian Stepanovites–Sweetina group probably occupied the trophic position of primary consumers. The relation of the isotopic composition of conodonts and host carbonates allow us to reconstruct the low to moderate pelagic primary bioproductivity of the Early Kazanian basin in the Volga-Vyatka region. According to the obtained data, a negative trend in the change of carbon isotope composition of conodont elements in the Late DevonianMiddle Permian interval was noted. This trend coincides with the decrease in carbon dioxide content in the atmosphere. The δ13C of conodonts could be related to the atmospheric carbon dioxide content through the intensity of carbon isotope fractionation by phytoplankton. Conclusions. The relatively low pelagic primary bioproductivity of the Early Kazanian marine basin in the Volga-Vyatka region was reconstructed. Conodonts of the Stepanovites–Sweetina group in the pelagic trophic network of the Kazanian basin occupied the position of primary consumers feeding on phytoplankton with a light carbon isotope composition. This light carbon isotope composition may have been caused by a relatively low phytoplankton growth rate and, indirectly, with a low atmospheric carbon dioxide content in the Early Kazanian time. The assumed dependence of δ13C of Prioniodinida conodonts on the atmospheric carbon dioxide content can be used for approximate estimation of carbon dioxide content variations for some stratigraphic intervals.